Two Grand Old Ladies Face to Face: The United Kingdom and the United States of America Constitutions Compared - Patrono, Mario; Frosini, Justin O (Victoria University of Wellington Law Review, 2015)
This article discusses the Constitution of the United Kingdom and then draws some comparisons between it and the Constitution of the United States of America. It touches on issues such as how the United Kingdom's commitment to parliamentary sovereignty has been affected by the country's relationship with the European Union.